361 HLA DRB1 ALLELES IN AFRICAN-AMERICANS WITH EARLY RHEUMATOID ARTHRITIS: PRELIMINARY RESULTS FROM 207 SUBJECTS IN THE CLEAR STUDY. (1st January 2005) - Hughes, L. B.; Alarcón, G. S.; Conn, D.; McNicholl, J.; Jonas, B.; Callahan, L.; Smith, E.; Gilkeson, G.; Howard, G.; Moreland, L. W.; Bridges, S. L.
Abstract : Purpose: HLA DRB1 alleles containing the shared epitope (*0101, *0102, *0401, *0404, *0405, *0408, *0413, *1001) are associated with susceptibility and severity of RA in Caucasians, but their role in African-Americans with RA is less clear. Methods: The Consortium for the Evaluation of African-Americans with Early Rheumatoid Arthritis (CLEAR) is a NIAMS-funded registry with the goal of recruiting 400 African-Americans with early RA (< 2 years disease duration) to allow analysis of genetic and nongenetic factors associated with radiographic severity at 3 years disease duration. CLEAR is a multicenter study, with subjects being recruited from UAB, Emory University, University of North Carolina, and Medical University of South Carolina. The subjects enrolled in the CLEAR cohort to date have a mean (± SD) age at disease onset of 51.2 ± 13.3 years and mean baseline disease duration 13.5 ± 7.2. ˜ 81% of subjects are female and ˜ 73% are RF-positive. HLA DRB1 genotyping has been performed on the initial 207 subjects using the Atria Genetics, South San Francisco, CA, AlleleSEQR DRB1 reagents and protocol. Results: Approximately 61% of subjects have 0 copies of shared epitope-containing HLA DRB1 alleles, 33% have 1 copy, and 6% have 2 copies. Thus the shared epitope is much less common in African-Americans with RA than Caucasians with RA. Conclusions: This is the largest study to date describing the shared epitope status in African-Americans with RA and the first study in focusing on those with early RA. Most African-Americans in the CLEAR Registry presenting with early RA do not have HLA DRB1 alleles containing the SE. Genotyping of geographic region-specific controls is currently in progress, which should help to clarify the role of the HLA DRB1 in RA susceptibility in African-Americans. Correlation of HLA DRB1 alleles with baseline radiographs of the hands and feet is also under way, which should help delineate the role of HLA DRB1 alleles in disease severity and outcomes in African-Americans.